2017
DOI: 10.4194/1303-2712-v17_4_02
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Supercritical carbon dioxide (SE) and Soxhlet extractions with hexane (HE) were used to obtain oil from skins, scales and bones of bigeye tuna (Thunnus obesus). SE was done at a previously optimized conditions of 40° C and a pressure of 25 MPa with a gas-flow rate of 10 kg/h. By SE, 85.6, 83.2 and 87.7% of oil was recovered (extractability) from skins, scales and bones, respectively, considering the HE extraction to be the total oil. The oils obtained with SE and HE were evaluated for their physicochemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
(44 reference statements)
0
9
1
Order By: Relevance
“…These results were not much different from previous studies, which showed that there was no significant difference in fatty acid composition of fish oil obtained from salmon and tuna by-products using organic solvents and SC-CO 2 (Ahmed et al, 2017;Ferdosh et al, 2015;Park et al, 2019…”
Section: Fatty Acid Composition Of Fish Oilscontrasting
confidence: 50%
See 1 more Smart Citation
“…These results were not much different from previous studies, which showed that there was no significant difference in fatty acid composition of fish oil obtained from salmon and tuna by-products using organic solvents and SC-CO 2 (Ahmed et al, 2017;Ferdosh et al, 2015;Park et al, 2019…”
Section: Fatty Acid Composition Of Fish Oilscontrasting
confidence: 50%
“…Specifically, carbon dioxide used as a supercritical fluid can solve the problem of the hazards of solvent, denaturation of components and complexity of the extraction process because of its nontoxicity, has a low critical point (T c = 31℃, P c = 73 bar), and easy volatilization after extraction (Roh et al, 2008). Supercritical carbon dioxide (SC-CO 2 ) has also been proved to be an efficient method of oil extraction from biomass in our previous studies (Ahmed et al, 2017;Franklin et al, 2020;Haq, Getachew, et al, 2017;Roh et al, 2008;Roy et al, 2020). In this study, anchovy oil was extracted using the SC-CO 2 extraction as a clean process for the high valorization of anchovies and comparative experiments were conducted with both anchovy oil extracted using an organic solvent and commercial oils containing EPA and DHA.…”
mentioning
confidence: 99%
“…Overall color differences (∆E*) of the organic solvent extracted oils showed lower value comparing the SC-CO 2 extracted oils which might be interlinked with the lightness value of the samples (Jeong, Lim, Cho, & Lim, 2003). Some other researchers also reported that SC-CO 2 extracted oils from seafood samples showed more lightness than the organic solvents extracted oils (Ahmed et al, 2017;Haq et al, 2017;Lee et al, 2017). The color is contributed by impurity, pigment content, oxidation compound, and the processing conditions (Sathivel, 2005 found in the SC-CO 2 -extracted oils at 45°C and 20 MPa, whereas the lowest value was found in the Soxhlet-extracted oils.…”
Section: Physicochemical Propertiesmentioning
confidence: 90%
“…Rubio-Rodríguez et al (2012) extracted omega-3 PUFA rich salmon oil by different methods and reported that SC-CO 2 extraction at 40°C and 25 MPa showed reduced oxidation and lower impurities. Ahmed, Haq, Cho, and Chun (2017) conducted research on the extraction of tuna by-products oil using SC-CO 2 extraction and Soxhlet apparatus whereas he found superior quality oil in SC-CO 2 extraction regarding physicochemical and oil stability parameters. Atlantic salmon by-products oils extracted by SC-CO 2 extraction showed better stability parameters and biofunctional properties than organic solvent extracted oils (Haq et al, 2017).…”
Section: Pufasmentioning
confidence: 99%
“…The PUFAs are potential for maintaining proper human health and decreasing the risk of atherosclerosis, hypertension, neurological degeneration of aging, tumors cell growth, inflammation, improve insulin sensitivity, optimize visual signaling, and maintain bone mass. Fish oils are characterized by a rich source of long chain PUFAs including eicoapentanoic acid (EPA) and docosahexaenoic acid (DHA) which play a crucial role in the prevention of various health problems such as cardiac problem, hypertension, stroke, obesity, depression, cancer, premature aging etc [8][9][10].…”
Section: Introductionmentioning
confidence: 99%